Practical Ansible configuration management from start to finish - Sesto, Vincent (Apress, 2022)
Get ready to go from the basics of using Ansible to becoming proficient at implementing configuration management in your projects. This book begins with the basics of Ansible, providing you with details on how to install and configure your environment while working with different Ansible modules from the command line. Next, it introduces you to working with Ansible tasks and organizing configuration code into playbooks. You'll then learn how to extend playbooks further, using roles and templates within the configuration code. Author Vincent Sesto then extends your knowledge further by covering custom Ansible modules using Python and Linux shell scripts and demonstrating how you can start to keep your secret values encrypted and secure using Ansible Vault. You'll also develop Ansible roles with the use of Ansible Galaxy to reuse existing roles that others have created. This updated edition reflects changes added in the latest version of Ansible (2.9). It also includes an expanded chapter on testing Ansible using Molecule and managing large server environments using applications like Ansible Tower.
Includes index. - Includes bibliographical references
Keywords: Configuration management; Open source software; Web site development; Computer programming; Gestion de configurations; Logiciels libres; Sites Web; Développement; Programmation (Informatique); computer programming